Repurposing existing drugs for new uses: a cohort study of the frequency of FDA-granted new indication exclusivities since 1997 - Babak Sahragardjoonegani; Reed F. Beall; Aaron S. Kesselheim; Aidan Hollis (Journal of Pharmaceutical Policy and Practice, 2021)
Background Drug repurposing (i.e., finding novel uses for existing drugs) is essential for maximizing medicines’ therapeutic utility, but obtaining regulatory approval for new indications is costly. Policymakers have therefore created temporary indication-specific market exclusivities to incentivize drug innovators to run new clinical investigations. The effectiveness of these exclusivities is poorly understood. Objective To determine whether generic entry impacts the probability of new indication additions. Methods For a cohort of all new small-molecule drugs approved by the FDA between July 1997 and May 2020, we tracked new indications added for the subset of drugs that experienced generic entry during the observation period and then analyzed how the probability of a new indication changed with the number of years since/to generic entry. Results Of the 197 new drugs that subsequently experienced generic entry, only 64 (32%) had at least one new indication added. The probability of a new indication addition peaked above 4% between 7 and 8 years prior to generic entry and then to dropped to near zero 15 years after FDA approval. We show that the limited duration of exclusivity reduces the number of secondary indications significantly. Conclusion Status quo for most drug innovators is creating novel one-indication products. Despite indication-specific exclusivities, the imminence of generic entry still has a detectable impact on reducing the chances of new indication additions. There is much room for improvement when it comes to incentivizing clinical investigations for new uses and unlocking existing medicines’ full therapeutic potential.